The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.48550/arxiv.2209.08504
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unveiling hidden stellar aggregates in the Milky Way: 1656 new star clusters found in Gaia EDR3

Abstract: We report 1,656 new star clusters found in the Galactic disk (|b|<20 degrees) beyond 1.2 kpc, using Gaia EDR3 data. Based on an unsupervised machine learning algorithm, DBSCAN, and followed our previous studies, we utilized a unique method to do the data preparation and obtained the clustering coefficients, which proved to be an effective way to search blindly for star clusters. We tabulated the physical parameters and member stars of the new clusters, and presented some interesting examples, including a globu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…An even higher number have recently been discovered in EDR3 data (Castro-Ginard et al 2022), while other authors have reported similar numbers of new discoveries (e.g. Hao et al 2022;He et al 2022). These new cluster candidates discovered in Gaia data now rival in number the clusters known before its launch.…”
Section: Introductionmentioning
confidence: 77%
“…An even higher number have recently been discovered in EDR3 data (Castro-Ginard et al 2022), while other authors have reported similar numbers of new discoveries (e.g. Hao et al 2022;He et al 2022). These new cluster candidates discovered in Gaia data now rival in number the clusters known before its launch.…”
Section: Introductionmentioning
confidence: 77%
“…Since there is no relevant proper motion parameter in the data, we have to only compare the mean parameters within 5σ (whereσ is the uncertainty listed in both catalogs for each quantity) using sky coordinates. To eliminate as many OCs as possible that have already been found and obtain OC candidates that have not been unnoticed before, we consider an OC to be positionally matched to a cataloged one if their astrometric mean parameters (l, b, , µ α , µ δ ) are compatible within 5 σ (where σ is the uncertainty quoted in both catalogs for each quantity) which is consistent with He et al (2022a), He et al (2022c) and Hao et al (2022a). The list of previously published sources including LP, Ferreira Series, CWNU, Hao Series, UBC, and so on is presented in Table 1.…”
Section: Cross-matchmentioning
confidence: 99%
“…Since a real OC should have clear main sequence features on the CMDs, reference Cantat-Gaudin et al ( 2020) and He et al (2022a), to screen out the most reliable candidates, we performed manual visual inspections on spatial distributions (SDs), proper motion distributions (PMDs), parallax distributions (PDs) and vs µ α , and their isochrone fits results to further check the quality of candidate clusters.…”
Section: Comprehensive Analysis Based On Visual Insectionmentioning
confidence: 99%
See 2 more Smart Citations